A situação fiscal dos municípios maranhenses após a Lei de Responsabilidade Fiscal: uma avaliação com ênfase nas receitas próprias - SOARES JUNIOR, Eden do Carmo (2016)
The Fiscal Liability Law (FLL) brought a set of measures intended to ensure a more responsible fiscal management in the country with an emphasis on achieving local revenues by subnational units. The study brings an economic data panel of the Maranhão State and its municipalities and demonstrates how it impacts on local public finances. For the theorical foundation, the formation of the Brazilian tax system is investigated as well as aspects related to the theory to taxes. The study also addresses the fical federalism, the distribution of tax sources by federal entities, and the verification of the units responsible for the public policies management. It presents the Brazilian economic scenario that gave rise to the implementation of the Real Plan in the 1990s and the reforms associated with it that resulted in the creation of the FLL. It stands out as a general objective of the research the examination of how Maranhão municipalities have adapted to the new standards of accountability brought by the FLL in fiscal management, and espcially if they have managed to raise their exclusive revenues. We used to instruments to achieve this goal: the Fiscal Management Firjan Index (FMFI) and the Tax Revenues Achievement Indicator (TRAI). In issues such as public investment, the state's municipalities are well placed when compared to others of the Federation. However, the evaluated city halls are at a lower level than the national average regarding the generation of the own revenue. Nevertheless, Maranhão municipalities managed to raise their private income after the introduction of the FLL, although this increase is concentrated in cities that received extraordinary invesments in particular sectors of the economy like Santo Antonio dos Lopes and Bacabeira.